Frequency of Stroke and Factors Leading to It in Old Age Patients With Hypertension - Wahab, Saman; Ullah, Sami; khan, Abbas; Imran Khan, Muhammad; Mubarak, Shazia (Biological and Clinical Sciences Research Journal, 2025)
Stroke is a major cause of disability and mortality among hypertensive elderly patients. Understanding its frequency and associated risk factors is crucial for prevention and management. Objective: This study aimed to determine the frequency of stroke and identify associated risk factors among hypertensive old aged patients. Methodology: A cross-sectional study was conducted at a tertiary care hospital over six months. Participants included 150 hypertensive patients (86 males, 64 females) with a mean age of 57.4 ± 7.1 years. Data were collected through structured interviews and medical record reviews, capturing sociodemographic details, behavioural factors (smoking), clinical history (diabetes, cardiovascular disease, dyslipidemia, prior stroke), and physical measurements (BMI, blood pressure). Stroke diagnosis was confirmed using WHO criteria, supported by clinical and imaging evidence. Descriptive statistics and logistic regression were used for analysis, with significance set at p < 0.05. Results: The frequency of stroke was 10.7% (n=16). Stroke cases were more prevalent in individuals over 60 years (81.2%), males (75.0%), smokers (56.2%), and those with obesity (56.2%). Comorbid conditions such as diabetes (50.0%) and dyslipidemia (50.0%) were significantly higher in stroke patients compared to non-stroke cases (20.1% and 23.1%, respectively). A family history of stroke was reported in 43.8% of stroke patients, compared to 8.2% in non-stroke participants. Conclusion: Stroke remains a significant health concern among hypertensive patients, with a prevalence of 10.7%. Key risk factors include advanced age, male gender, smoking, obesity, and comorbid conditions such as diabetes and dyslipidemia. These findings underscore the need for targeted interventions, including smoking cessation programs, weight management strategies, and stricter control of metabolic conditions. Routine screening and public health education should be prioritized to mitigate stroke risk in this vulnerable population.